PENGEMBANGAN E-LKPD BERBASIS DISCOVERY LEARNING TERINTEGRASI ETNOSAINS PADA MATERI ASAM BASA - Astuti; Desy Kurniawati (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop an e-LKPD based on discovery learning integrated with ethnoscience on acid-base material. The background of this study is based on the problem of low student understanding of the acid-base concept, the lack of visual and interactive media, and the limited use of technology in chemistry learning. This research is a design research study using the development model by Plomp, which consists of three stages: preliminary research, development/prototyping, and assessment phase. The results of the study show that the developed learning media is valid with an Aiken’s V value of 0.94, after being validated by seven experts (four content validators and three media validators). The practicality test indicates that the media is highly practical, with a practicality level of 98.5%. Meanwhile, the effectiveness test shows that the media is effective, proven by the learning outcomes of students using the e-LKPD being significantly higher than those in the class that did not use the developed e-LKPD. Therefore, the e-LKPD based on discovery learning integrated with ethnoscience on acid-base material that was developed is feasible to be used as an innovative alternative in chemistry learning to improve student learning outcomes.